(untitled) (Mustansiria Dental Journal, 2018)
Background: Nutritional status is the mirror image of health and one of its most accurate indicators. Normal salivary gland functions are essential for maintenance of oral health. Salivary flow rate and composition which could be influenced by nutritional status. The aim of this study was to investigate the effect of nutritional status on Streptococcus mutans and their relations to dental caries. Materials and methods: Stimulated saliva was collected from 28 children with an age 6 years old. Those randomly selected children were divided into wellnourished and chronic malnourished children according to their age, weight and height indicators. Dental caries examination of primary teeth was assayed following the criteria of WHO. Microbiological assessment of Streptococcus mutans was done after measuring the salivary flow rate. Results: No significant differences were found between well-nourished and chronic malnourished children in caries experience. Chronic malnourished children had a significant lower salivary flow rate and higher mean counts of salivary Streptococcus mutans than that of well-nourished children. Significant correlations were found between nutritional status with flow rate and Streptococcus mutans. Conclusion: Early identification of malnourished children will lower the prevalence of dental caries and enhance their quality of life.